2020
DOI: 10.3390/e22050547
|View full text |Cite
|
Sign up to set email alerts
|

Reference Evapotranspiration Modeling Using New Heuristic Methods

Abstract: The study investigates the potential of two new machine learning methods, least-square support vector regression with a gravitational search algorithm (LSSVR-GSA) and the dynamic evolving neural-fuzzy inference system (DENFIS), for modeling reference evapotranspiration (ETo) using limited data. The results of the new methods are compared with the M5 model tree (M5RT) approach. Previous values of temperature data and extraterrestrial radiation information obtained from three stations, in China, are used as inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…However, depending on the station and test year, this similarity becomes even closer. All the test years and stations showed an improvement from temperature to radiation or mass-transfer-based combination except for the Prosper station, which is in agreement with the findings of Adnan et al [15]. On the other hand, the Prosper station showed the best improvement for the SVM model for radiation-based approaches.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, depending on the station and test year, this similarity becomes even closer. All the test years and stations showed an improvement from temperature to radiation or mass-transfer-based combination except for the Prosper station, which is in agreement with the findings of Adnan et al [15]. On the other hand, the Prosper station showed the best improvement for the SVM model for radiation-based approaches.…”
Section: Discussionsupporting
confidence: 89%
“…The ET o calculation is a complex process due to a large number of associated meteorological variables, and it is hard to develop an accurate empirical model to overcome all the complexities of the process [15]. Over the last few decades, machine learning (ML) techniques have attracted the interest of streams of researchers around the globe to overcome the ET a estimation complexity.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature indicates that numerous studies have examined the application of several AI models for estimating ET 0 [17][18][19][20][21][22][23][24][25][26][27][28]. In more detailed state-of-the-art, Yin et al [26] introduced a new hybrid AI model dependent on the hybridization of a genetic algorithm with a kernel model i.e., a support vector machine (GA-SVM) for modeling daily ET 0 in China using several daily climatic variables including T max , T min , wind speed (U 2 ), relative humidity (RH), and solar radiation (SR).…”
Section: Introductionmentioning
confidence: 99%
“…The finding of that study showed that all models provide satisfactory results in terms of several performance criteria. Adnan, et al [6] predicted reference evapotranspiration (ET0) in the China by evaluating different data driven models based solely on-air temperature data. Although there is plethora of studies that have already explored the potential use of several intelligent models at different sub-filed of water resources management, the present study aims to bring into light the potential of some other novel intelligent models which to the best of our knowledge are scarcely applied in the field of climatology, particularly in the air temperature prediction.…”
Section: Introductionmentioning
confidence: 99%